Integrin-mediated leukocyte adhesive interactions - Chavakis, T.; Preissner, K. T. (Hämostaseologie, 2005)
Leukocyte recruitment to sites of inflammation, infection or vascular injury is a complex event that is orchestrated by a tightly coordinated sequence of interactions between leukocytes and cells of the vessel wall, especially endothelial cells. These interactions are controlled by the expression and activation of various adhesion receptors and protease systems.This review will focus on novel aspects of the regulation of integrin-dependent leukocyte adhesion by haemostatic factors. Here, so-called non-haemostatic properties of endogenous proteins such as high molecular weight kininogen, urokinase receptor, urokinase, as well as plasminogen and its cleavage product angiostatin in leukocyte adhesion and transmigration will be summarized. The crosstalk between haemostatic factors and inflammatory reactions may contribute to a better understanding of inflammatory vascular disorders and to the development of novel therapeutical concepts.
Keywords: Integrin; haemostasis; inflammation